2008
DOI: 10.1128/iai.01139-07
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 2-Mediated Interleukin-8 Expression in Gingival Epithelial Cells by the Tannerella forsythia Leucine-Rich Repeat Protein BspA

Abstract: Tannerella forsythia is a gram-negative anaerobe strongly associated with chronic human periodontitis. This bacterium expresses a cell surface-associated and secreted protein, designated BspA, which has been recognized as an important virulence factor. The BspA protein belongs to the leucine-rich repeat (LRR) and bacterial immunoglobulin-like protein families. BspA is, moreover, a multifunctional protein which interacts with a variety of host cells, including monocytes which appear to respond to BspA through T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 35 publications
1
65
0
Order By: Relevance
“…Thus, they appear to be ideal ligands for a pattern recognition receptor. Interestingly, BspA interacts also with other pattern recognition receptors, such as the Toll-like receptor TLR2 (41), and recent findings suggest that Lrr domains are needed for this interaction (42). Thus, it may be that Lrr domains can serve as recognition motifs for other pattern recognition receptors as well.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they appear to be ideal ligands for a pattern recognition receptor. Interestingly, BspA interacts also with other pattern recognition receptors, such as the Toll-like receptor TLR2 (41), and recent findings suggest that Lrr domains are needed for this interaction (42). Thus, it may be that Lrr domains can serve as recognition motifs for other pattern recognition receptors as well.…”
Section: Discussionmentioning
confidence: 99%
“…This family, originally identified in Treponema pallidum, is comprised of proteins that are located on the cell surface (26,27). Furthermore, LRR TP proteins were shown previously to play a role in surface adherence and aggregation (26,37,38). AdpC contains six typical LRR motifs in which most of the leucine-like residues are conserved compared to the BspA protein of T. forsythia (37,42).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LRR TP proteins were shown previously to play a role in surface adherence and aggregation (26,37,38). AdpC contains six typical LRR motifs in which most of the leucine-like residues are conserved compared to the BspA protein of T. forsythia (37,42).…”
Section: Discussionmentioning
confidence: 99%
“…Although the identity of these components is currently unknown, an earlier study has demonstrated that T. forsythia S-layer proteins also mediate attachment to and invasion of KB epithelial cells (Sabet et al, 2003). Interestingly, T. forsythia whole cells and their components have been shown to activate the pattern recognition receptor Toll-like receptor (TLR)2 (Hasebe et al, 2004;Kikkert et al, 2007;Onishi et al, 2008), and PI3K is also a downstream target of TLR2 activation. Thus, the contribution of BspA in invasion and host cell signalling in the context of the bacterial whole cell could not be discerned in this study.…”
Section: Tyrosine Kinase(s) and Pi3k Are Involved In T Forsythia Invmentioning
confidence: 99%